Recent evidence on agricultural efficiency and productivity in China: a metafrontier approach; Neue Anhaltspunkte für Effizienz und Produktivität in der chinesischen Agrarproduktion: Eine Metafrontier Untersuchung - Supawat Rungsuriyawiboon; Xiaobing Wang (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2007)
Economic reform in China helped transform the structure and volume of agricultural production and resulted in significant changes in efficiency and productivity. This paper measures agricultural technical efficiency (TE) and total factor productivity (TFP) in China by allowing producers operating under their own technologies. A metafrontier function approach is applied using a panel data set on 28 provinces during 1991-2005. The provinces are categorized into advanced-technology and low-technology provinces. Based on the metafrontier estimation, TFP growth is decomposed into TE change (TEC), technical change (TC) and scale efficiency change (SEC). This information is useful for policy makers to design suitable policies in enhancing agricultural TE and TFP growth in China. Our major findings indicate that TC was mostly attributed to Chinese agricultural TFP growth throughout the period of study. SEC and TEC exhibited negative effects to TFP growth for the advance- and low-technology provinces, respectively. Most of the advanced-technology provinces exhibited higher TE than the low-technology provinces. The comparatively low TE scores in the low-technology provinces imply that the low-technology provinces were operating far from the metafrontier. The fluctuation of TE measured with respect to the metafrontier function indicates it is possible that Chinese agricultural TFP growth can be improved through the improvement of TE. The results also show that labor and fertilizer still make important contributions to output, and thus improving the quality of farmers and applying modern physical inputs is also crucial to TFP growth. – – Chinas wirtschaftliche Reformen halfen der Landwirtschaft, die Struktur und dem Umfang der landwirtschaftlichen Produktion umzubauen. Signifikante Erhöhungen der Effizienz und der Produktivität waren die Folge. Die vorliegende Arbeit misst technische Effizienz (TE) und total factor productivity (TFP) in China unter der Annahme individueller Technologien der Landwirte. Mit Hilfe eines Paneldatensatzes für 28 Provinzen über den Zeitraum 19912005 wird ein metafrontier Ansatz angewandt. Die Provinzen werden in technologisch fortschrittliche und weniger entwickelte Regionen eingeteilt. Auf der Basis des metafrontier Ansatzes wird das TFP Wachstum in Änderung der technischen Effizienz (TEC), technischen Fortschritt (TC) und Änderung der Skaleneffizienz (SEC) zerlegt. Daraus abgeleitete Informationen sind für die Entwicklung angepasster Politiken zur Förderung technischen Fortschritts und TFP-Wachstums in der chinesischen Landwirtschaft erforderlich. Zentrale Ergebnisse der Analyse zeigen, dass das Wachstum der TFP hauptsächlich durch den technischen Fortschritt erklärt wird. Dagegen weisen SEC und TEC negative Effekte auf das Wachstum der TFP in beiden Provinz-Untergruppen auf. Die Mehrzahl der technisch weiterentwickelten Provinzen weisen eine höhere technische Effizienz als die weniger entwickelten Regionen auf. Die vergleichsweise niedrigen TE-Werte der letzteren deuten auf die weiter entfernte Lage dieser Provinzen von der Metafrontier hin. Die Ergebnisse zeigen, dass Chinas TFP-Wachstum durch eine Steigerung der TE erhöht werden kann. Des Weiteren leisten die Faktoren Arbeit und Düngemittel einen wichtigen Beitrag zur Produktion. Somit sind zusätzlich die Ausbildung der Landwirte und die Bereitstellung moderner Produktionsmittel für die Steigerung der TFP von Bedeutung.
urn:nbn:de:gbv:3:2-1678
Keywords: Q16; Q18; P27; 330; Metafrontier; Agriculture; China; Technical Efficiency; Total Factor Productivity; Metafrontier; Landwirtschaft; Stochastic Frontier Schätzung; China; Technische Effizienz; Technischer Fortschritt; Skaleneffizienz; Total Factor Productivity